Influence of Liposomes and Niosomes on the In Vitro Permeation and Skin Retention of Finasteride: Permeation study of finasteride-entrapped vesicles - Daneshamouz, Saeid; Tabbakhian, Majid; Tavakoli, Naser; Jaafari, Mahmoud Reza (Iranian Journal of Pharmaceutical Sciences, 2005)
In this work we sought to determine whether vesicles (liposomes/niosomes) were able to enhance finasteride concentration in the dermis layer, including the pilosebaceous units (PSU). Such enhancement could be beneficial in the treatment of some androgen-related skin disorders. Hamster flank skin was used to study 3Hfinasteride permeation via vesicles and a hydroalcoholic solution (HA). The drug-containing vesicles were composed of dimyristoyl phosphatidylcholine (DMPC) or egg lecithin: cholesterol: dicetyl phosphate (liposomes) and polyoxyethylene alkyl ethers (Brij® series) or sorbitan monopalmitate (Span 40): cholesterol: dicetyl phosphate (niosomes) and were prepared by the film hydration technique. Determination of finasteride content by HPLC showed 80-97% drug entrapment efficiency in the vesicles. The amount of 3H-finasteride penetrated into and permeated through hamster skin 24 h after topical application of vesicles ranged from 5.5 to 13% of the initial dose, compared to 24%, observed with HA (p<0.05). The amount of finasteride deposited within the different skin strata via gelstate Span 40 and lecithin vesicles was lower, when compared with liquid-state Brij97, Brij 76: Brij 97 and DMPC vesicles. The fraction of finasteride found in the dermis layer was greatest where DMPC liposomes were used (7.8%). The vesicles significantly reduced drug permeation as indicated by the flux of finasteride from vesicles (0.025-0.058 µg/cm2.h), where compared with the HA (0.13 µg/cm2.h), (p<0.01). This study demonstrated the potentials of liquid-state vesicles in reducing the percutaneous absorption of finasteride and increasing its concentration and retention in the dermis layer.